EFFECTIVENESS OF HYPNOTEACHING METHOD TO INCREASE STUDENT’S SKILLS ON CREATIVE THINKINGAND NOTION IN SOLUBILITY AND SOLUBILITY PRODUCTS MATTER - Herdizal Rianda; Noor Fadiawati; Nina Kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This research described the effectiveness of hypnoteaching method to increase student’s skills on creative thinking and notion in solubility and solubility products matter.  Subject of this research was 32 students of XI IPA2 SMAN 13 Bandarlampung in academic years 2011-2012.  This research used the one shot chase study. Effectiveness of hypnoteaching learning was measured based on the increasing affective value before and after aplicated it on difined time. The results showed that it could increased both skills.  The creative thinking increased for the first to fifth observation was 21%, 30%, 34%, 44%, and 48%, changed from low to sufficient level.  It’s mean that just a small amount to limit a half of students mastered its.  The other one, notion skill increased for the first to fifth meeting was 27%, 45%, 61%, 70% and 65%, changed from low to good level. It’s mean that just a small amount to big amount of students mastered its.Keywords: hypnoteaching, creative thinking skill, notion skill, pre-experiment, one-shot chase study